Growth and phytochemical composition of Andrographis paniculata (Burm.f.) Wall. ex Nees in relation to different light intensities, photoperiod and pruning - Omar, Nur Faezah (2018)
Vegetative stage of Andrographis paniculata when grown under Malaysia conditions is found to be short as compared to those grown in India. Both quality and quantity of light will affect plant development. In addition, pruning is one of the way to extend vegetative stage and delay flower formation. Therefore, this study was conducted to determine the effect of different light intensities, photoperiod and pruning frequency on growth and phytochemical composition of A. paniculata. Four weeks old seedlings were arranged in a split plot design with three replications where the main plots were shade levels while the sub plots were pruning frequencies. Plant samples were taken and analyzed for their morphological, physiological, and phytochemical changes. The Amax of A. paniculata was achieved at light intensity of 1000 μ mol m-2s-1. A significant interaction effect was found on N, P and Mn content. Higher andrographolide content obtained from plant with 50% shade and single pruning. Conversely, total phenolic and total flavonoid content decreased under shade levels for all pruned and non-pruned plants. Optimum shoot dry weight was obtained in single pruned plant at 50% shade levels, thus shade levels of 50% and single pruning have been chosen for photoperiod study. Photoperiodism of A. paniculata was further studied under four different long day photoperiods (12, 13, 14 and 15 h). The maximum growth rate of plant height (6.96 cm/week) was obtained from plant exposed to 13 h light. Flower development was influenced by long day treatments with the plant exposed to 13 h light prolonged the days to flower by 2.1 days compared to 12 h. The lowest percentage of flowering was detected under 13 h. Besides, leaf dry weight of 13 h photoperiod improved by 26% as compared to 15 h. The result of 13 h photoperiod were further tested in determination of suitable plant age for initiation of light treatment. The initiation of 13 h light length were tested from 3rd, 5th and 7th week after transplanting. The total leaf area of 3rd WAT (week after transplanting) had 10.5% greater as compared to normal photoperiod, 7.2% higher as compared to 5th WAT and 7.3% higher as compared to 7th WAT. The flowering percentage was 29.6% higher from plant without light treatment as compared to 3rd WAT. Leaf dry weight recorded from 3rd WAT was greater by 10.6 %, 6.9% and 7.2% as compared to normal photoperiod, 5th WAT and 7th WAT. Total plant fresh weight and dry weight were improved with initiation of light at 3rd WAT. Total phenol and total flavonoid content were improved with light initiation at 3rd WAT. Micrographs of SEM showed that development of floral meristem involved at least three stages which consisted of vegetative stage, transition stage and development of flower parts. The flower initiation of plant exposed to light at 3rd and 5th WAT was delayed compared to control and 7th WAT. In conclusion, growth and phytochemical composition of A. paniculata can be altered by growing the crop under suitable light intensities, photoperiod induction and undergone pruning.